Legal rights for the Turag: rivers as living entities in Bangladesh. Issue 2 (December 2020) - Islam, Mohammad Sohidul; O'Donnell, Erin
Abstract : In 2019, Bangladesh joined the ever-growing list of countries to recognize rivers as living entities with legal rights. The Bangladesh Rivers case is another example of advocacy from the Supreme Court in Bangladesh, and the article explores the relationship between the executive and the judiciary, and the ongoing role the judiciary has played in water law reform. The Court based its decision on a novel reading of the Constitution, linking the legal rights of the rivers to the public trust doctrine and the human right to a healthy environment. This foundation is itself potentially controversial, and the new legal status of the rivers may set their interests against those of the people who live along and rely upon them. By making comparisons between this case and similar decisions in India and Colombia, the Bangladesh Rivers case can be seen as part of the transnational movement to grant legal rights to rivers.